The art of educating free, able and creative people: The theories of Dr. Broddi Jóhannesson - Þórlindsson, Þórólfur (Tímarit um uppeldi og menntun, 2017)
Dr Broddi Jóhannesson was one of the most influential leaders in education in Iceland in the twentieth century. He played a leading role in the revolutionary changes that occurred in teacher education in the sixties and seventies. He shaped teachers’ education as headmaster of the teachers’ training college, and later, as the first rector of the newly founded university responsible for teacher education in Iceland, not to mention the fact that he was a legendary teacher who influenced generations of teachers for decades. Broddi Jóhannesson was directly involved in the development of educational policy and teacher education in Iceland through his work on several governmental committees that rewrote the educational policy on teacher education. Finally, he was a pioneer in pedagogical and psychological sciences in Iceland. Broddi Jóhannesson was one of the founding fathers of the national science fund. He was among the first Icelandic social scientists to publish articles in international journals. He served as the editor for Menntamál, the only scholarly journal exclusively devoted to education.Jóhannesson showed a remarkable consistency in his prolific work acrossvarious roles and immeasurable tasks in all areas of education. In this paper I argue that this consistency was rooted in a carefully worked out and a unique theoreticalframework that Broddi Jóhannesson developed early in his career. While he did not find the time to present his theories in a comprehensive and a systematic manner, many of their key elements are displayed in his writings. I try to show how his theoretical framework was a unique mixture of ideas drawn from classical humanism, science, critical theories and traditional knowledge and wisdom from Icelandic farmers and fishermen. Broddi Jóhannesson emphasized the scientific method as a key element in the demarcation of science. He was especially interested in the experimental method as a model for scientific inquiry. At the same time he stressed the importance of skepticism and the right to ...